Restoration of the vertical dimension of occlusion in a patient with occlusal colapse – Clinical case report (Research, Society and Development, 2024)
Oral rehabilitation in patients with partial tooth loss and occlusal collapse often requires restoration of the occlusal vertical dimension (OVD). In such cases, treatment demands specific planning and strategies to achieve a new occlusal relationship. The use of a semi-adjustable articulator (SAA) provides greater clinical planning security, however, mounting becomes more complex due to changes in occlusal planes caused by posterior tooth loss. This article aims to detail the planning for OVD restoration in occlusal collapse patients, describing an alternative SAA mounting approach. Methodology: This study is a descriptive analytical case report, conducted at the Oral Rehabilitation Clinic of the Universidade Estadual do Oeste do Paraná in Cascavel, Brazil. Case Report: A 60-year-old male patient, fair-skinned, complained of frequent fractures of restorations and significant aesthetic dissatisfaction. The patient had posterior tooth loss, generalized wear and alteration in OVD. Definitive oral rehabilitation was achieved through fixed prostheses on implants in edentulous posterior regions and fixed prostheses on remaining teeth. Final Considerations: In oral rehabilitations for patients with occlusal collapse, correct SAA mounting is crucial for effective planning of facial dimensions, restoring OVD predictably and physiologically.